Experimental induction of self-focused attention via mirror gazing: Effects on body image, appraisals, body-focused shame, and self-esteem. (September 2019) - Barnier, Ellise M.; Collison, James
Highlights: Focus on a disliked part via mirror gazing at 10 cm negatively impacts body image. Viewing features broadly via mirror gazing at 100 cm has no effect on body image. The effects of self-focused attention can be induced in non-clinical samples. Targeting mirror behaviour may be key for those with body image disturbances. Abstract: Cognitive and behavioural models of body dysmorphic disorder posit that selective self-focused attention via mirror gazing plays a key role in the aetiology and maintenance of the disorder. However, there is little empirical support for these theoretical claims. This study aimed to induce self-focused attention via mirror gazing to examine the proposed theoretical effects on body image, distress, body-focused shame, and self-esteem. Fifty-one non-clinical participants (78.43% female) were randomly allocated to one of the two conditions: low self-focused attention (i.e., looking into a mirror placed 100 cm/ 39 in away) vs. high self-focused attention (i.e., focusing on a disliked part in a mirror placed 10 cm/ 4 in away). Following 5 min of mirror gazing, the high self-focused attention condition experienced decreased satisfaction with appearance, perceived attractiveness, and self-esteem, and increased distress about appearance, distress about disliked parts, urges to change appearance, and body-focused shame. Approaching the mirror from a distance appeared to have no effect. Findings are consistent with theories suggesting that self-focused attention and mirror behaviours might contribute to the development of body dysmorphic disorder and maintain its psychological effects.